Enhancing the Believability of Character Behaviors Using Non-Verbal Cues - Desai, Neesha; Szafron, Duane (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2012)
Characters are vital to large video game worlds as they bring a sense of life to the world. However, background characters are known to rarely exhibit any sign of motivated behavior or emotional state. We want to change this by assigning these characters emotions that can be identified through their non-verbal behavior. We feel the addition of emotion will allow players to feel more connected to the game world and make the game world more believable. This paper presents the results of an experiment to test two ways of conveying emotion: 1) through a character’s gait and 2) through a character’s interactions with the game world. Results from the experiment suggest that a combination of gait and interactions is the most effective method to convey emotion.